The Effect of Flexible Bronchoscopy on Anxiety in Children - Türkeli, Ahmet (Turk Thorac J, 2016)
OBJECTIVES: Flexible bronchoscopy (FB) is a semi-invasive diagnostic tool that allows direct visualization of the airways. The use for diagnostic and therapeutic purposes in children is incrasing with the developments in modern anesthesia. Irrespective of the type of the invasive diagnostic procedure, these interventions are known to cause anxiety in patients. The aim of our study was to evaluate the anxiety and depression status in children hospitalized for bronchoscopy and to investigate the effects of FB. MATERIAL AND METHODS: Thirty children hospitalized for FB and 30 controls, aged 7 to 16 years, were enrolled in this study. Anxiety was evaluated with the “Hospital anxiety and depression scale” (HADS)” besides other parameters recorded. RESULTS: The mean HADS anxiety scores in the patient and control groups were respectively 10.1 (3.5) and 2.7 (1.3) (p= 0.001). The mean HADS depression scores were respectively 8.8 (3.7) and 2.2 (1.1) (p= 0.001). Among the patients, 50% had anxiety and 53.3% had findings while none in the control group showed signs of anxiety and depression. A positive correlation was found between the age and, anxiety and depression scores in patients’ groups (respectively r(1)= 0.257; p= 0.05 and r(2)= 0.288; p= 0.02). CONCLUSION: Anxiety was demonstrated in nearly half of the children hospitalized for bronchoscopy. It has been observed that behavioral and physical problems may be encountered in approximately 40–60% of children who feel generalized anxiety before anesthesia, during the preoperative, postoperative period, and subsequent periods. These results suggest that the detection of children with increased anxiety and indicate the individual requirements can be assisted pharmacological and psychological supports.